The media and their informative role in the face of the coronavirus disease 2019 (COVID-19): validation of fear perception and magnitude of the issue (MED-COVID-19) - Mejia, C.R. (2020)
Introduction: The media play an important role in the dissemination of information on the 2019 novel coronavirus disease (COVID-19) pandemic. However, it is important to measure whether the population is receiving information that calms it down, as well as whether such news are in accordance with the magnitude of the issue. Objective: To validate a questionnaire that measures the perception of the media and their informative role in the face of COVID-19 pandemic. Methods: A validation process for a questionnaire that measures the perception of the magnitude of this issue and whether it generates fear was carried out. The validation was performed by means of a literature search. Moreover, a first version of the scale was developed, which was assessed by 30 experts (physicians, epidemiologists, among others). After this, an exploratory factor analysis and descriptive statistics were performed. Results: Our scale had 13 initial items; however, one of them was eliminated because of its unsatisfactory level of statistical adequacy. Exploratory factorial analysis and parallel analysis suggested three factors. Results of the KMO coefficient (0.833) and the Bartlett’s test of sphericity (4998.5; gl = 66; p<0.001) were acceptable and significant, which justify the exploratory factorial analysis. The correlation between the factors was >0.4 and robust analyses revealed a satisfactory factorial structure (X2=88.0; p= 0.001; IFC=0.968; GFI=0.992; TLI=0.937; RMSEA=0.123). In the descriptive statistics of the 12 final items, moderate and significant correlations between the items were reported (> 0.5). Conclusion: We generate a scale to validate the perception of how people receive information from the media. Thus, this scale can be used to measure the informative role of the media regarding the COVID-19 pandemic, and may even serve for other similar public health emergencies.